Awake spinal fusion: a retrospective analysis of minimal invasive single level transforaminal lumbar interbody fusion done under spinal anaesthesia in 150 cases - Rangnekar, Ameya; Anand, Mani K.; Goparaju, Praveen; Chugh, Amit; Shetty, Abhijith; Raut, Saijyot; Kundnani, Vishal (International Journal of Research in Orthopaedics, 2022)
Background: Spinal anaesthesia carries the advantage of having rapid onset, lesser blood loss, early recovery and hospital stay as compared to general anaesthesia. The present study evaluated outcomes of awake spinal fusion i.e., minimal invasive single level transforaminal lumbar interbody fusion (MIS-TLIF) under spinal anaesthesia. Current study is a retrospective analysis of prospectively collected data carried to assess patient related outcome benefits for a single level transforaminal lumbar interbody fusion done under spinal anaesthesia. Methods: Patients who fit deemed criteria not responding to 6 weeks of conservative treatment to lumbar degenerative pathologies underwent MIS-TLIF. The demographic data, visual analogue pain scale (VAS), Oswestry disability index (ODI), blood loss, time from entering operation theatre to time of incision, time of bandaging to exit from operation theatre, time of stay in post anaesthesia care unit (PACU), duration of surgery, nausea/vomiting, urinary retention, requirement of analgesics, duration of stay in hospital, peri-operative complications, fusion rate and satisfaction score were compiled and assessed. Results: 150 patients were operated with MISTLIF under spinal anaesthesia. VAS and ODI score improved significantly at final follow up (p<0.05). The mean duration of surgery was 148±18.24 minutes and blood loss were 109.64±110.45 ml. The average time from entering OT to incision and bandaging to exit was respectively 27.32±8.44 and 6.43±3.28 minutes. Mean PACU time was 36.74±6.32 minutes while duration of stay averaged 1.58±0.67 days. Post operative analgesia requirement was in 10.6% patients and radiographic fusion was observed in 96.6% patients. 90.6% patients were fully satisfied with spinal anaesthesia. Conclusions: Awake spinal fusion should be considered as a novel surgical approach with newer minimal invasive surgical techniques and regional anaesthesia to improve patient satisfaction and overall surgical outcome.